Dietary spirulina platensis and chlorella vulgaris effects on survival and haemato-immunological responses of clarias gariepinus juveniles to aeromonas hydrophila infection - Raji, Ameenat Abiodun; Junaid, Olawale Quazim; Oke, Mushafau Adebayo; Taufek, Norhidayah Mohd; Muin, Hasniyati; Abu Bakar, Noor Hidayati; Alias, Zazali; Milow, Pozi; Simarani, Khanom; Razak, Shaharudin Ab (Bioflux SRL, 2019)
This study investigated the effects of Spirulina platensis and Chlorella vulgaris on the growth, non-specific immunity and survival of Clarias gariepinus. C. gariepinus juveniles were infected with Aeromonas hydrophila after a 16-week feeding period with 5 different diets which served as replacements for fishmeal diet. The diets are 50% C. vulgaris (CL50%), 75% C. vulgaris (CL75%), 50% S. platensis (SP50%), 75% S. platensis (SP75%), and control (100% fishmeal). Fish (n=225; 41.85± 0.05 g) were randomly divided into fifteen tanks (150 L capacity each) with triplicate groups of 15 fish per tank. CL50% had the most significant (P<0.05) weight gain (233.72±0.02 g), relative growth rate (558.15±0.57%), feed conversion ratio (0.89±0.01) and protein efficiency ratio (5.81±0.03) compared to the control, while there were no significant differences (P>0.05) in growth performance among the algae treatments. Similarly, lysozyme and respiratory burst activity and post-challenge haemoglobin, haematocrit, red blood cells, serum total protein, albumin and higher density lipoprotein cholesterol were significantly higher (P<0.05) in CL50% treatment. The present study indicates that replacing 50%-75% of fishmeal with C. vulgaris or S. platensis could improve the growth and confer significant protection against A. hydrophila in the algae-fed C. gariepinus. © 2019, BIOFLUX SRL. All rights reserved.